A Potential Anticancer Mechanism of Finger Root (Boesenbergia rotunda) Extracts against a Breast Cancer Cell Line. (5th September 2022) - Widyananda, Muhammad Hermawan; Wicaksono, Septian Tri; Rahmawati, Kurnia; Puspitarini, Sapti; Ulfa, Siti Mariyah; Jatmiko, Yoga Dwi; Masruri, Masruri; Widodo, Nashi
Abstract : Breast cancer is the most common type of cancer women suffer from worldwide in 2020 and the 4th leading cause of cancer death. Boesenbergia rotunda is an herb with high potential as an anticancer agent. This study explores the potential bioactive compounds in B. rotunda as anti-breast cancer agents using in silico and in vitro approaches. The in silico study was used for active compound analysis, selection of anticancer compound candidates, prediction of target protein, functional annotation, molecular docking, and molecular dynamics simulation, respectively. The in vitro study was conducted by measurement toxicity, rhodamine 123, and apoptosis assays on T47D cells. Based on the KNApSAcK database, B. rotunda contained 20 metabolites, which are dominated by chalcone and flavonoid groups. Seven of them were predicted to have anticancer activity, namely, sakuranetin, cardamonin, alpinetin, 2S-pinocembrin, 7.4′-dihydroxy-5-methoxyflavanone, 5.6-dehydrokawain, and pinostrobin chalcone. These compounds targeted proteins related to cancer progression pathways such as the PI3K/Akt, FOXO, JAK/STAT, and estrogen signaling pathways. Therefore, these compounds are predicted to inhibit growth and induce apoptosis of cancer cells through their interactions with MMP12, MMP13, CDK4, JAK3, VEGFR1, VEGFR2, and KCNA3. Anticancer activity of B. rotunda through in vitro study confirmed that B. rotunda extract is strong cytotoxic and induces apoptosis of breast cancer cell lines. This study concludes that Boesenbergia rotunda has potency as an anticancer candidate.